2020
DOI: 10.1186/s12966-020-00976-x
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of physical activity, sedentary time, and sleep duration and their associations with depressive symptoms and other mental health problems in children and adolescents: a systematic review

Abstract: Background: For optimal health benefits, the Canadian 24-Hour Movement Guidelines for Children and Youth (aged 5-17 years) recommend an achievement of high levels of physical activity (≥60 min of moderate-to-vigorous physical activity), low levels of sedentary behaviour (≤2 h of recreational screen time), and sufficient sleep (9-11 h for children or 8-10 h for adolescents) each day. The objective of this systematic review was to examine how combinations of physical activity, sedentary time, and sleep duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
166
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(189 citation statements)
references
References 61 publications
16
166
0
7
Order By: Relevance
“…Physical activity (PA), sedentary behavior (SB), and sleep are key components of daily movement behaviors [1]. Ample evidence has con rmed the importance of all three behaviors for physical, mental, and social health in children and adolescents [2][3][4][5]. Experts recommend that children and adolescents spend at least 60 minutes in moderate-to-vigorous PA (MVPA) [6], accumulate no more than 2 hours of recreational screen time (ST) [7], and get enough sleep (9-11 hours for children and 8-10 hours for adolescents) every day [8] to maximize their health.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA), sedentary behavior (SB), and sleep are key components of daily movement behaviors [1]. Ample evidence has con rmed the importance of all three behaviors for physical, mental, and social health in children and adolescents [2][3][4][5]. Experts recommend that children and adolescents spend at least 60 minutes in moderate-to-vigorous PA (MVPA) [6], accumulate no more than 2 hours of recreational screen time (ST) [7], and get enough sleep (9-11 hours for children and 8-10 hours for adolescents) every day [8] to maximize their health.…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, non-compositional studies have reported associations between these outcomes and sleep, ST, and physical activity (21, 24, 26, 29), but none accounted for the mutually exclusive and compensatory nature of these behaviours, which are relative to one another over a 24-hour day. Recently, this has been examined with studies showing that youth who met multiple guidelines for sleep, ST, and MVPA were likely to have better mental health than peers meeting fewer recommendations (20,32,64). However, as our sample had low prevalence of meeting physical activity and sleep guidelines, it is unlikely that this explanation would hold true with our data.…”
Section: Discussionmentioning
confidence: 99%
“…For the rst time, the combined associations between physical activity, sedentary behaviour, and sleep with youth mental health were recently reviewed (32). Meeting public health recommendations for all three behaviours was associated with better mental health when compared to youth who did not meet any of the recommendations, and a dose-response gradient was observed between the number of recommendations achieved and more positive mental health (32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity (PA), sedentary behavior (SB), and sleep are key components of daily movement behaviors [1]. Ample evidence has con rmed the importance of all three behaviors (independently of each other) for physical, mental, and social health in children and adolescents [2][3][4][5][6][7]. Experts recommend that children and adolescents spend at least 60 minutes in moderate-to-vigorous PA (MVPA) [8], accumulate no more than 2 hours of recreational screen time (ST) [9], and get enough sleep (9-11 hours for children and 8-10 hours for adolescents) every day [10] to maximize their health.…”
Section: Introductionmentioning
confidence: 99%